N'-[1-(2-Hydroxy-5-methylphenyl)ethylidene]benzenesulfonohydrazide - Laila, M.; Ali, Hapipah Mohd; Puvaneswary, S.; Robinson, W.T.; Ng, Seik Weng (International Union of Crystallography, 2008)
The two independent mol-ecules in the asymmetric unit of the title compound, C15H16N2O3S, are each linked by an N - H⋯Osulfon-yl hydrogen bond into a linear chain that runs along the shortest axis of the triclinic unit cell. The hydr-oxy groups are engaged in intra-molecular hydrogen bonding and the amino N atom shows pyramidal coordination.